Pentingnya Berelasi Dengan Bhatara Hyang Guru Melalui Sanggah Kemulan Dalam Mencapai Kelepasan - Kadek Yuli Wahyu Astini (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2020)
To worship God Almighty and its manifestations, Balinese Hindu society is very synonymous with its sacred buildings. Where the holy building is a symbol as well as an intermediary medium for human communication with God. This makes holy places have a very important position in Hinduism. If in the community a holy place is called a temple. However, it is different in the household / family that the holy place is called Sanggah / Mrajan. In general, Sanggah is a holy place to worship God and its manifestations and the ancestors who have been purified. Therefore Sanggah / Mrajan is not only an intermediary medium between God and humans, but also as an intermediary medium for the Hindu community to communicate with their ancestors, one of which is through the Sanggah Kemulan. Every human being born in the world, of course, already has a debt called Tri Rna. Where the debt will be paid through Panca Yadnya. One of the debts that must be paid is Pitra Rna which is paid through Pitra Yadnya and Manusia Yadnya. To pay this debt every Hindu community always relates to Bhatara Hyang Guru through the Sanggah Kemulan. This is intended to establish a harmonious relationship between families who are still living with God and also their ancestors. So that because of this, humans will achieve happiness during their lifetime